(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article discusses the phenomenon and significance of the adaptation of each individual to the environment from a socio-psychological point of view. In addition, social adaptation, in turn, is a type of interaction between an individual (social group) and the social environment, during which certain requirements are imposed on certain participants. That is, it is about the processes of adapting the subject to the requirements of society, compliance with social requirements by the group due to prohibitions for certain actions.